Medical Ethnobiology and Indigenous Knowledge System Found In Darai Ethnic Group of Chitwan, Nepal - Poudel, Manisha; Singh, Nanda Bahadur (Journal of Institute of Science and Technology, 2016)
The present study focuses on traditional usages of animals and plants species for medicinal purpose and indigenous knowledge system existent in Darai ethnic group of Mangalpur VDC, Chitwan, Nepal. A total of 28 animal species and 76 plant species were found to be used by Darai people to treat 22 and 36 different ailments, respectively. Darai people have their own indigenous knowledge for making various bamboo products and fishing equipments and local drink (moat/muna). The existence of knowledge associated with animals and plants and their medicinal utility is currently threatened mainly due to modernization, easy access to health services, lack of interest of youngsters, few local healers and fading of ethnic characters of Darai ethnic group. Thus, documentation of such knowledge has become an urgent need. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 103-111